International vs. national female tennis players: a comparison of upper and lower extremity functional asymmetries - Chapelle, L.; Bishop, C.; Clarys, P.; D'Hondt, E. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Asymmetries have been reported to negatively impact sport performance. This study examined the magnitude and direction of whole-body functional asymmetry in international versus national female tennis players. METHODS: Ten internationally and twelve nationally ranked tennis players participated. Upper extremity functional asymmetries (or side-to-side performance differences) were evaluated using handgrip strength, seated shot-put throw and plate tapping. Lower extremity functional asymmetries were determined using the single leg countermovement jump, single leg forward hop test, 6 m single leg hop test, 505 changes of direction (time and deficit), and Y-balance test (anterior, posteromedial, posterolateral). ANOVAs were used to compare the dominant (overall best or fastest result of a specific test) versus non-dominant performance values (best or fastest result of the corresponding extremity) within the internationally versus nationally ranked players. Functional asymmetry magnitudes differences (expressed as a precentage) were examined using Mann-Whitney U tests. Kappa coefficients examined the consistency as to which extremity performed dominantly across tests. RESULTS: Significant asymmetries for every upper and lower extremity test were found. The functional asymmetry magnitude was significantly (P=0.020) higher on the single leg forward hop test for the nationally (6.3%) versus internationally ranked players (2.9%). Kappa coefficients showed perfect levels of consistency regarding all upper extremity tests (k=1.00), indicating true limb dominance whereas more variance was found as to which lower extremity performed dominantly across tests (k range=-0.067-0.174). CONCLUSIONS: The included female tennis players displayed significant whole-body functional asymmetries. Poor consistency as to which lower extremity performed dominantly across tests warrants individual asymmetry monitoring.